PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA KARYAWAN DI NEO HOTEL GROUP JAKARTA - Richi Setria; Bonifasius M.H Nainggolan (LPPM Universitas Asa Indonesia, 2020)
This study aims to examine the effect of Compensation, Organizational Culture and Leadership on job satisfaction at Neo Hotel Group. Respondents were taken from 55 employees of the Neo Hotel Group. The sampling technique uses saturated sampling technique. Data analysis techniques used multiple linear regression analysis. The results of the analysis can be concluded that Compensation, Organizational Culture and Leadership have positive and significant effects both simultaneously and partially on Employee Job Satisfaction. For that every Department must pay attention to salaries and wages according to national standards. Organizational Culture employees by giving appreciation to employees who excel so as to create good job satisfaction.